Synthesis and Room Temperature Structural, Optical, Electrical Properties of Holmium Doped GdMn2O5 Multiferroics. (1st March 2023) - Swathi, D.; Yadav, Nand Kishor; Praveen, P.; Swamy, N. Kumar; Kumar, N. Pavan
Abstract : Multiferroic materials with the compositional formulae Gd1-x Hox Mn2 O5 (x = 0, 0.1, 0.2, 0.3, and 0.4) were prepared by the conventional solid-state reaction method. The structural analysis has been carried out by X-ray diffraction technique which confirms the orthorhombic structure with the Pbam space group. The optical properties have been studied by UV Visible, FTIR, and Raman spectra. The energy gap that was calculated using UV visible absorption spectra shows that the material is semiconducting in nature. The observed 14 Raman and 17 IR active modes are attributed to the relative motions of corresponding atoms and by increasing the doping concentration of Ho, the emergence of phonon shifting was observed which suggests the possible multiferroic coupling behaviour. The electrical properties including dielectric constant, dielectric loss, and ac conductivity at room temperature indicate the spin-lattice coupling.